Pengembangan Media Pembelajaran Augmented Reality Berbasis Assemblr Edu untuk Meningkatkan Hasil Belajar IPAS Siswa Sekolah Dasar - Sholicha, Asrilia Putri; Ratnaningrum, Ika (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – The aim of this research is to develop innovative learning media based on Augmented Reality (AR) using smartphones through the Assemblr Edu application for science instruction.Method – This study is categorized as research and development (R&D), with the goal of producing a product and testing its effectiveness. The development model employed is ADDIE, which includes five stages: analysis, design, development, implementation, and evaluation. Findings – The results indicate that validation by material experts yielded a score of 90.27%, while validation by media experts scored 87.5%. The combined average score from both expert assessments is 89.1%, suggesting that the Assemblr Edu-based learning media is highly feasible for classroom use. In terms of effectiveness, the average pre-test score was 55.65 and the post-test score was 81.74, with an N-gain value of 0.59, which falls within the medium effectiveness category. Research Implications – The findings of this study suggest that Assemblr Edu-based learning media is a valid and effective tool for enhancing elementary students’ understanding of science concepts, particularly in the topic of food chains. Its integration of Augmented Reality provides an interactive and engaging learning experience, making abstract content more accessible. The positive results from expert validations and learning outcomes indicate that this media can be confidently implemented in classroom settings as a supplementary instructional resource. Moreover, its use supports the development of digital literacy among students by leveraging mobile technology in education. Future applications may extend its use to other science topics or interdisciplinary learning contexts.